Hormone therapy : a clinical handbook - Sherif, Katherine (Springer New York, 2013)
Hormone Therapy: A Clinical Handbook provides a comprehensive overview on hormone replacement therapy, with a range of key features that differentiate it from other titles on the topic. This concise, handy title presents an interdisciplinary approach to the subject, acknowledging that sex hormones affect more than reproductive organs and hot flushes for a deeper understanding of how hormones function. The authors provide a breadth and depth of practical prescribing experience, including many helpful tables and algorithms as well as directions for prescribing hormone therapy in the most effective and safest ways possible.  Targeted and easy to read, Hormone Therapy: A Clinical Handbook offers all clinicians the state-of-the-art information they need to prescribe hormone therapy and hormone replacement therapy.